2014
DOI: 10.3171/2014.8.focus14373
|View full text |Cite
|
Sign up to set email alerts
|

Single-level anterior cervical discectomy and fusion versus minimally invasive posterior cervical foraminotomy for patients with cervical radiculopathy: a cost analysis

Abstract: Object Patients suffering from cervical radiculopathy in whom a course of nonoperative treatment has failed are often candidates for a single-level anterior cervical discectomy and fusion (ACDF) or posterior cervical foraminotomy (PCF). The objective of this analysis was to identify any significant cost differences between these surgical methods by comparing direct costs to the hospital. Furthermore, patient-specific characteristics were also considered for their effect on component costs. Methods After obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 13 publications
0
69
0
2
Order By: Relevance
“…); 1 trial protocol article and 1 expert opinion article were excluded. The remaining 10 studies were finally included, comprising 3 prospective randomized controlled trails (RCT) and 7 retrospective comparative studies (RCoS). Details of these studies are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…); 1 trial protocol article and 1 expert opinion article were excluded. The remaining 10 studies were finally included, comprising 3 prospective randomized controlled trails (RCT) and 7 retrospective comparative studies (RCoS). Details of these studies are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Three RCoS reported cost or cost‐effectiveness of both groups in the treatment of single‐level cervical radiculopathy. Mansfield et al reported that the average cost of an ACDF was 89% more than a PCF with 3 years follow‐up time. Alvin et al reported that the cost‐utility ratio of PCF group was 39% lower than that of ACDF group with 1 year follow‐up time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The explanation for this is most likely the high costs of implants used in ACDF. Mansfield et al 18 reported an average difference of $3872 between ACDF and FOR, with $3143 of this difference contributable to costs in the operating room (including materials). Tumialán et al 20 found a difference of $6508 between FOR and ACDF with plating.…”
Section: Introductionmentioning
confidence: 99%